Pengaruh Kelekatan Ayah terhadap Regulasi Emosi pada Remaja Akhir di Kota Padang - Fauziah Kautsar Rizki; Rahmadianti Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to determine the effect of paternal attachment on emotional regulation in late adolescents in Padang City. Paternal attachment is seen as a crucial factor in developing children's emotional regulation skills, particularly during late adolescence, which is the transitional phase toward adulthood. Late adolescence is a crucial period in an individual's psychological development, where the ability to manage and express emotions appropriately determines their mental and social well-being. A strong emotional attachment to a father is believed to provide a foundation of emotional security that helps adolescents regulate their emotional responses to various life pressures and challenges. This study used a quantitative approach with a purposive sampling technique and involved 272 late adolescent respondents in Padang City as a sample. Data were collected through a questionnaire designed to measure the level of paternal attachment and adolescents' emotional regulation skills. Data collection was carried out with attention to the validity and reliability of the instrument so that the research results can be scientifically accounted for. Data analysis was conducted using descriptive and inferential statistics to identify the relationship and influence between paternal attachment variables and emotional regulation. The results showed that the level of father attachment in late adolescents was in the moderate category at 53.3%, while their level of emotional regulation was in the high category at 42.3%. These findings indicate that although father attachment did not reach the high category for most, adolescents' emotional regulation abilities were relatively good. Further statistical analysis revealed that there was an influence of father attachment on emotional regulation in late adolescents, but this influence was very weak. This indicates that although father attachment contributes, there are many other factors that play a role in shaping adolescents' emotional regulation abilities, such as attachment to the mother, peer support, education, and individual experiences.